Efektivitas Pengenalan Bahasa Isyarat Huruf Hijaiyah untuk Anak Tuna Rungu di SLB Dharma Wanita Situbondo - Aisyatin Kamila (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
This study aims to describe the effectiveness of introducing sign language for the hijaiyah letters in the learning process for deaf children at the Dharma Wanita Special Needs School in Situbondo based on the experiences of female PPL students. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews. The subjects of the study were 5 female PPL students who directly taught the hijaiyah letters using sign language and 1 supervising teacher at the PPL location, namely at the Dharma Wanita Special Needs School in Situbondo. The results of the study indicate that the use of sign language for the hijaiyah letters is effective in helping deaf children recognize and understand Arabic letters, especially through a visual approach and consistent hand movements. Teachers also expressed that learning became more interesting and participatory. However, there are several challenges such as limited media and the need for longer time in delivering the material. This study concludes that sign language for the hijaiyah letters is a potential alternative learning strategy for deaf children.